Prevalence of Venereal Syphilis Among Youth Aged Between 18-35 Years Attending Kisenye Health Centre IV, Kampala District. - Magezi, Ronald (Student's Journal of Health Research Africa, 2021)
Background: Syphilis is an infection caused by a spirochete Treponema pallidum transmitted by direct contact with a syphilitic sore on the skin and in the mucous membrane. The study was undertaken to determine the prevalence of venereal syphilis among youth aged between 18- 35years, it also assessed the predisposing factors, prevention, and control measures of venereal syphilis Methodology: This was a cross-sectional study conducted among 96 respondents in Kisenyi Health Centre IV between the month of January and February 2020. A simple random sampling method was used to select the 96 respondents whereby the respondents were selected on a first come first serve basis. The questionnaire interview schedule was used for data collection, Venous blood was collected and the Treponema pallidum hem-agglutination assay test kits were used in the diagnosis. Results: Out of the 96 respondents who were enrolled in study 20(20.8%) were males and 76(76.2%) were females. The majority of the respondents who were affected were females 04(4.2%) in the age (18-35). The most predisposing factors to venereal syphilis was Ignorance, the use of drugs, poverty, co-infection, little knowledge about the use of a condom, as well as urban residence were also revealed to be some of the predisposing factors to acquire the disease. Conclusion: the prevalence of venereal syphilis in kisenyi health centre IV was found to be higher among the youth especially between the age of 18-25 years. Recommendations: The health care providers should do thorough assessments to address common diseases especially cases of venereal syphilis among the youth between 18-35 years.